Tea intake and total body bone mineral density of all ages: a Mendelian randomization analysis - Xing, Chen; Tan, Yanrong; Ni, Wentao (Frontiers in Nutrition, 2024)
Background There is increasing evidence indicating that tea intake affects bone mineral density levels; however, the causality between tea intake and bone mineral density is inconclusive. This study aimed to assess the causal relationship between tea intake and total body bone mineral density (TB-BMD) through two-sample Mendelian randomization (MR) analysis. Methods We conducted a two-sample MR approach to estimate the potential causal effects of tea intake on TB-BMD at all ages in a European population. The analyses were performed using summary statistics obtained for single-nucleotide polymorphisms (SNPs), identified from a genome-wide association meta-analysis of tea intake (N = up to 447,485 individuals) and from the GEnetic Factors for OSteoporosis (GEFOS) Consortium’s genome-wide association meta-analysis (N = up to 56,284 individuals), with baseline data collected in 2018 and populations derived from the European ancestry. The association between each SNP and TB-BMD was weighted by its association with tea intake, and estimates were combined mainly using an inverse-variance weighted meta-analysis. In addition, we explored the potential causal effects between green tea intake, herbal tea intake, and TB-BMD. Results The MR analysis revealed that genetically determined tea intake exerts a causal impact on TB-BMD, with an odds ratio (OR) of 1.204 (95% CI: 1.062–1.366, p = 0.004), especially in the age group of 45–60 years (OR = 1.360, 95% CI: 1.088–1.700, p = 0.007). No horizontal pleiotropy and heterogeneity were observed. However, there was no causal effect of tea intake on TB-BMD in the age groups of 0–15, 15–30, 30–45, and over 60 years. In the subgroup analysis, when green tea intake was regarded as the exposure factor, no salient associations were found between green tea consumption and TB-BMD (IVW p = 0.368). Similarly, there was also no causal association between herbal tea intake and TB-BMD (IVW p = 0.264). Conclusion The findings of this study support the evidence that tea consumption increases bone density and reduces the risk of osteoporosis in the age group of 45–60 years within the European population.